2000
DOI: 10.1053/rapm.2000.5672
|View full text |Cite
|
Sign up to set email alerts
|

Epidural catheter tip cultures: Results of a 4-Year audit and implications for clinical practice

Abstract: We concluded that a significant proportion of epidural catheter tips may be "culture positive" after removal. It is suggested that this probably represents colonization of the skin at the catheter insertion site and subsequent contamination of the catheter tip on removal of the catheter. The large number of "culture positive" tips in the absence of clinically identifiable epidural space infection suggests that routine culture of epidural catheter tips is clinically irrelevant in the vast majority of cases, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
2
29
0
4
Order By: Relevance
“…One patient with a BMI of 58.4 kg.m )2 desaturated to 90% after only 55 s, and to 82% in 65 s. These findings are broadly in agreement with Jense et al [3] who studied time to desaturation after 5 min of pre-oxygenation. They found normal sized patients desaturated after 364 s and morbidly obese patients after 163 s.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…One patient with a BMI of 58.4 kg.m )2 desaturated to 90% after only 55 s, and to 82% in 65 s. These findings are broadly in agreement with Jense et al [3] who studied time to desaturation after 5 min of pre-oxygenation. They found normal sized patients desaturated after 364 s and morbidly obese patients after 163 s.…”
supporting
confidence: 89%
“…Patients undergoing surgery for malignancies are also at risk as a result of anatomic factors. Patients undergoing head and neck surgery are at higher risk for aspiration pneumonia and infections by skin and oral mucosal flora [2,3]. Patients with biliary tract obstruction are usually treated with stents or diverting procedures that enable colonisation of the biliary tract with intestinal flora which increases the risk of postoperative infection.…”
Section: A Replymentioning
confidence: 99%
“…Cuvillon et al have reported colonization of 57 % of femoral catheters in 208 patients after 48 h, 3 of which had infection requiring no antibi-otics [21]. The rate of colonization was 28.8 % in 1443 epidural catheter series of Simpson at al and the incidence was not found to be related with the catheter duration [22]. Although bacterial analysis was not performed after the removal of the catheters, we did not observe any local infection signs or neurological deficit at discharge attributable to the blocks in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Um estudo prospectivo realizado com 1.443 pacientes, demonstrou que 28,8% dos pacientes obtiveram cultura positiva do cateter peridural por, pelo menos, um microorganismo, sugerindo que há uma significante proporção de cultura positiva representando a colonização da ponta do cateter peridural pela pele e sua contaminação durante a retirada, sem relevância clínica para infecção (23) .…”
Section: Discussionunclassified
“…Para reduzir o risco de colonização ou contaminação do cateter peridural, as seguintes medidas devem ser adotadas: escovação das mãos, uso da barreira de precaução máxima pelo anestesista; preparo da pele do paciente com antisséptico alcoólico na implantação do cateter; uso de curativo semiperméavel na inserção do cateter; uso de filtro antibacteriano durante a permanência do cateter peridural no paciente; vigilância do curativo e do local de inserção do cateter na pele, controle da temperatura do paciente e monitorização das queixas do paciente, como a ocorrência de sinais de meningismo (18)(19)(22)(23)(24)(27)(28)(29)(30) .…”
Section: Discussionunclassified